1. Before the Erection of Great George Street. 2. Before the Erection of Parliament Street Plan Of A Portion Of Westminster Between 1734 And 1748. (Tufts Archival Research Center, 2005)
This illustration is from Walter Thornbury "Old and new London, a narrative of its history, its people, and its places, vol. 3"